The novel of “my idiot brother” by Agnes Danovar (book review) - Wajdi, Majid; Adnyana, I Komang Putra; Dewi, Komang Ayu Trian; Dewi, Kadek Bintang Sri; Arini, Komang Pipit; Artini, Ni Kadek; Prathivi, Pande Putu Githa Sari; Ariani, Ni Luh Putu Yoni (Journal of Language, Literature, Social and Cultural Studies, 2023)
The purpose of this project is (1) to describe the intrinsic elements, (2) to describe the moral value, (3) to describe the strengths and weaknesses of the novel My Idiot Brother. The method used in the analysis is the document study method. The results  of this project are several moral values ​​that the readers can learn such as (1) honesty, (2) authentic values, (3) moral of responsibility, (4) moral of independence, (5) moral of courage, (6) realistic and critical. The novel also has the strength of presenting an interesting storyline in a relaxed style that is easy for the readers to understand. There are also some mistakes in typing this novel. The novel is interesting to read because it has a storyline that is easy to understand and there are many life lessons that the readers can take from each story presented.